2021
DOI: 10.1186/s13643-021-01651-3
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of diagnostic sleep studies for obstructive sleep apnoea: a systematic review protocol

Abstract: Background Obstructive sleep apnoea (OSA) is a significant public health problem affecting a large proportion of the population and is associated with adverse health consequences and a substantial economic burden. Despite the existence of effective treatment, undiagnosed OSA remains a challenge. The gold standard diagnostic tool is polysomnography (PSG), yet the test is expensive, labour intensive and time-consuming. Home-based, limited channel sleep study testing (levels 3 and 4) can advance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
0
6
0
3
Order By: Relevance
“…Several small single‐center studies have found clinical screening with subsequent selection for PSG to be more cost‐effective in deciding subsequent management 75 . A systematic review on the economic evaluation of diagnostic tests for OSA is underway, where the cost‐effectiveness of limited channel tests compared with PSG in the diagnosis of OSA will be conducted 76 . Ultimately, there is not a one‐size‐fit‐all strategy, and each region or country has to decide on the most appropriate screening strategy based on resource availability, OSA prevalence, and healthcare funding priorities.…”
Section: Discussionmentioning
confidence: 99%
“…Several small single‐center studies have found clinical screening with subsequent selection for PSG to be more cost‐effective in deciding subsequent management 75 . A systematic review on the economic evaluation of diagnostic tests for OSA is underway, where the cost‐effectiveness of limited channel tests compared with PSG in the diagnosis of OSA will be conducted 76 . Ultimately, there is not a one‐size‐fit‐all strategy, and each region or country has to decide on the most appropriate screening strategy based on resource availability, OSA prevalence, and healthcare funding priorities.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of using home-recorded data include reduced patient stresses, associated with travel and overnight hospital stays, plus a potential reduction in waiting times and clinical costs ( Collop et al, 2007 ). A systematic review is currently underway to determine the cost-effectiveness of limited channel tests compared to laboratory and home PSG in diagnosing OSA ( Natsky et al, 2021 ). Empirical studies support the use of limited channel tests carried out in the patients’ own home, suggesting similar efficacy, at lower costs, compared to PSG ( Masa et al, 2014 ; Corral et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Por ejemplo, en España no se han publicado estudios del coste social de esta patología, pero se estima que hay entre 1. 200.000 y 2.150.000 casos de SAOS, de los cuales solo el 25% están tratados (27). Además, su diagnóstico es importante porque su tratamiento permite una mejora de la calidad de vida, la reducción las tasas de accidentes automovilísticos y el riesgo de las complicaciones crónicas mencionadas anteriormente.…”
Section: Diagnóstico Del Saos Y Tipos De Estudios Del Sueñounclassified
“…La PSG se considera el estándar de oro para detectar casos de SAOS; sin embargo, es cara, requiere mucho tiempo y con frecuencia es inaccesible. Por lo tanto, se necesitan pruebas alternativas para realizar una preselección de casos potenciales (189,199,200).…”
Section: Resumen De La Evidenciaunclassified
See 1 more Smart Citation